Comparison of Use of Isoflurane or Sevoflurane for Anaesthesia Induced by Mask in Calves - Yakan, Selvinaz; Aksoy, Ozgur; Ermutlu, Celal Sahin (Acta Scientiae Veterinariae, 2020)
Background: Inhalation anaesthesia is an effective and reliable general anaesthesia method for inactivity, analgesia, and unconsciousness in extensive surgical procedures. Although widely used, especially in small animals, there are very few studies investigated the reliability and superiority of inhalation anaesthesia in surgical procedures for ruminants. This study intended to evaluate the anaesthetic effects of isoflurane and sevoflurane in different surgical cases with endotracheal intubation following the induction of anaesthesia using a calve-specific facemask, which is not yet a routine option in cattle. Materials, Methods & Results: The study was conducted on 14 calves, from new-born up to 3 months-old, that undergoing various surgical operations. The animals were divided into isoflurane and sevoflurane groups, and each group contained 7 animals. In all cases, atropine (0.04 mg/kg was administered intramusculer as premedication before 15 min from anaesthesia induction. For induction, the anaesthetic agent was given at an inspiratory concentration of 3-5% in the isoflurane group and at an inspiratory concentration of 5 - 7% in the sevoflurane group during 5 min via mask at 15min after atropine administration. In both groups, endotracheal intubation was performed (about 1-3 min) after of general anaesthesia symptoms starting. At 5min after induction, anaesthesia was continued at 1.5 - 3% in the isoflurane group and at 2.5 - 4% in the sevoflurane group during operation. The animals were monitored during anaesthesia and, anaesthetic effect, reaction of the calve, pronounced side effects, Heart Rate (HR), Systolic Arterial Blood Pressure (SABP), Diastolic Arterial Blood Pressure (DABP), Mean Arterial Blood Pressure (MABP), Respiration Rate (RR), Pulse Rate (PR), Arterial Oxygen Saturation (SpO2) were recorded at before anaesthesia, the premedication period, 5, 15, 30, 45, 60, 75 and 90min of anaesthesia. During anaesthesia, from the clinical parameters, mucosal capillary refilling time was evaluated by applying finger pressure to the oral mucosa. Mucous membrane color was determined by observing the oral mucosa. The time for palpebral reflex and swallowing reflex disappearance was measured and processed into individual forms. Anaesthesia induction and reanimation times were determined and recorded in the forms. After the operation, the return of the swallowing reflex and the time to stand up were recorded. During the operation, urination, defecation, salivation, vomiting, animal reactions, the shape and duration of the reamination period were recorded. In the isoflurane group anaesthesia induction was 3.71 ± 0.28 min, head movements started and came to the sterno- abdominal position at 4.57 ± 0.36 min, got up at 8.71 ± 0.42 min without assistance, meanwhile. In sevoflurane group, anaesthesia induction was 2.57 ± 0.20 min, head movements started and came to the sterno- abdominal position at 3.86 ± 0.40 min, the time to stand up was determined as 6.43 ± 0.29 min. During anaesthesia, HR, SABP, DABP, MABP, RR, PR, SpO2 findings were within physiological acceptable limits in 2 groups. In terms of indicators, there were no obvious differences in either group. The results revealed no significant difference between groups during anaesthesia. Discussion: The isoflurane and sevoflurane anaesthesia used in this study provided an adequate anaesthetic effect in calves characterized by adequate analgesia and muscle relaxation without any complications. The results of our study revealed that there was no significant difference between isoflurane and sevoflurane in calves. Both anaesthetic agents can be used safely for general anaesthesia in calves.